Manajemen Pelayanan Kampus Inklusif (Studi pada Pusat Studi dan Layanan Disabilitas Universitas Brawijaya) - Masadhe, Aldilla Reyndha; Sjamsuddin, Sjamsiar; Amin, Fadillah (Jurnal Ilmiah Administrasi Publik, 2021)
This type of descriptive research using qualitative methods aims to describe and analyze the implementation of inclusive campus service management (planning, organizing, actuating, controlling) and service quality for students with disabilities at Universitas Brawijaya as an Inclusive Campus along with the supporting factors and obstacle factors of services. The results showed that the service management of the Inclusive Campus at PSLD UB has been running well, preparing competent human resources and caring for students with disabilities, implementing work programs that support services for students with disabilities (recruitment of volunteers, providing counseling and companion tutors), conducting socialization and disability awareness training for academicians, and actively providing studies on disability issues. Inclusive Campus Services in terms of quality dimensions of public services are implemented quite well; including reliability, responsiveness, assurance, empathy, and physical evidence of services. The several obstacles in the implementation of the services are; the availability of facilities and infrastructures based on the Universal Design, the weakness of planning and supervision process in the building development that are friendly for people with disabilities.